Characterizing cell recruitment into isotropic and anisotropic biomaterials by quantification of spatial density gradients in vitro - Tortorici, Martina; Brauer, Erik; Thiele, Mario; Duda, Georg N.; Petersen, Ansgar (Frontiers in Bioengineering and Biotechnology, 2022)
The success of cell-free in situ tissue engineering approaches depends on an appropriate recruitment of autologous cells from neighboring tissues. This identifies cellular migration as a critical parameter for the pre-clinical characterization of biomaterials. Here, we present a new method to quantify both the extent and the spatial anisotropy of cell migration in vitro. For this purpose, a cell spheroid is used as a cell source to provide a high number of cells for cellular invasion and, at the same time, to guarantee a controlled and spatially localized contact to the material. Therefore, current limitations of assays based on 2D cell sources can be overcome. We tested the method on three biomaterials that are in clinical use for soft tissue augmentation in maxilla-facial surgery and a substrate used for 3D in vitro cell culture. The selected biomaterials were all collagen-derived, but differed in their internal architecture. The analysis of cellular isodensity profiles within the biomaterials allowed the identification of the extent and the preferential directions of migration, as well as their relation to the biomaterials and their specific pore morphologies. The higher cell density within the biomaterials resulting from the here-introduced cell spheroid assay compared to established 2D cell layer assays suggests a better representation of the in vivo situation. Consequently, the presented method is proposed to advance the pre-clinical evaluation of cell recruitment into biomaterials, possibly leading to an improved prediction of the regeneration outcome.